(Re)Examining Teenagers in Award-winning Australian Books for Young Readers - Hillel, Margot (Porównania, 2023)
The Children’s Book Council of Australia has been providing awards for young readers since 1946. Over the intervening years categories have been enlarged, acknowledging in part changes in readership and changes in conceptions of childhood and recognising a newer, defined category of ‘teenage’. However, prior to the introduction of the Older Readers category in 1982, there were a number of award-winning books which might well have fitted into that category. This paper will examine books for Older Readers 1972–2022 as a way of comparing Australian attitudes to ‘childhood’ across those decades, recognising that the material young people read often both reflects societal attitudes and reinforces them. What sort of childhood/teenagehood is portrayed, valorised or criticised in these books and have these aspects changed?